If it's not what You are looking for type in the equation solver your own equation and let us solve it.
26=(2x-6)(x+3)
We move all terms to the left:
26-((2x-6)(x+3))=0
We multiply parentheses ..
-((+2x^2+6x-6x-18))+26=0
We calculate terms in parentheses: -((+2x^2+6x-6x-18)), so:We get rid of parentheses
(+2x^2+6x-6x-18)
We get rid of parentheses
2x^2+6x-6x-18
We add all the numbers together, and all the variables
2x^2-18
Back to the equation:
-(2x^2-18)
-2x^2+18+26=0
We add all the numbers together, and all the variables
-2x^2+44=0
a = -2; b = 0; c = +44;
Δ = b2-4ac
Δ = 02-4·(-2)·44
Δ = 352
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{352}=\sqrt{16*22}=\sqrt{16}*\sqrt{22}=4\sqrt{22}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-4\sqrt{22}}{2*-2}=\frac{0-4\sqrt{22}}{-4} =-\frac{4\sqrt{22}}{-4} =-\frac{\sqrt{22}}{-1} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+4\sqrt{22}}{2*-2}=\frac{0+4\sqrt{22}}{-4} =\frac{4\sqrt{22}}{-4} =\frac{\sqrt{22}}{-1} $
| 4x-10=5x+30 | | 38x+1+37x+4=180 | | 26=(2x-6)(x-3) | | 1=m+2-2 | | 2(1/2-c)=12/5 | | 5x(6)=x+14+8x+9+x+17 | | 8x+5=5x+14=13 | | 3x+65=6x+15 | | x+89=85 | | X+24=8+7x | | 8x+5=5+14=13 | | 4(3x-5)=2(6x-10) | | X+15+3x-6+31=180 | | -2-21+4x=3-2(13-2x) | | 4a−6=9+a | | 23x+6=24x+1 | | 3x=x=6 | | 5(x-3)+2x+7=5x+6 | | 72.46+-88.1=x | | k+11=−3k−25+2k | | 8x+5x=5x+14=13 | | 6/16x+2(5+4)=-2+3/8x+20 | | 5(X-3)+7=5x+6 | | 5x=10x+34 | | 2(k-7)=5k | | 4p+1=-5 | | 10k+18=8k+4 | | r+31/2=42/3 | | -1/4x+6=2/3x-28 | | 86+x/3=90 | | 1-1k=6-2k | | X+870=7x |